Ukraine – ASEAN: new opportunities for strengthening partnership - Ірина Крупеня; Владилена Сокирська (Acta de Historia & Politica: Saeculum XXI)
The article provides a comprehensive scientific analysis of the current state of relations between Ukraine and ASEAN. The article considers promising areas of cooperation between them in the areas of food, agriculture, digitalisation, trade, energy, disaster management, demining, and socio-cultural cooperation. The author outlines Ukraine’s advantages in the field of agriculture and its ability to make a significant contribution to the sustainable supply of products to the ASEAN markets, given the production potential that far exceeds the needs of the domestic market.